Multi-criteria decision making analysis for responsible management of marine protected area in Semporna Sabah, Malaysia - Balan Nair, Madhavan (2016)
This study aims to develop a multi-criteria decision making model to analyse and investigate stakeholders’ preferences in Marine Protected Area Management towards a responsible management approach in Semporna, Sabah. This study was driven by the challenges faced by Sabah Parks in Managing Marine Protected Areas (MPAs). Sabah Parks have to deal with resource conflicts that include stakeholders’ interests in the decision-making process. The objectives of this study are: (i) to identify the current practices for the responsible management of the MPAs in Semporna; (ii) to identify critical decision making criteria related to the responsible management of these MPAs; (iii) to develop a decision-making model to analyse the decision criteria preference towards responsible management of the MPA in Semporna. This study adopts an exploratory sequential mixed methods approach through the lens of a critical realist employing multi-criteria decision-making as the underpinning theory. Data was collected from two main sources, namely, stakeholders, and documents related to MPA management. This data was used in three stages. In the first two stages, the modified Delphi method was used to gather the background of MPA management and criteria relevant to decision making towards responsible management from a group of selected experts. An in-depth interview was conducted during the first stage, while a structured questionnaire was applied during the second. Thematic analysis was applied on the data during the first stage. Criteria reduction using a geometric mean was performed for the questionnaire in the second stage. In the third stage, the questionnaire using pairwise comparison was fed to the Analytical Hierarchical Model (AHP) to analyse stakeholder decision-making preferences. The key contributions of this study in addressing responsible MPA management in Semporna, Sabah include: (i) a methodological contribution in analysing stakeholder preferences using AHP; (ii) the identification of decision objectives and critical criteria in the decision making process towards responsible MPA management; and (iii) acquiring deeper insights on stakeholders’ perceptions and choice of management alternatives towards responsible MPA management. This study provides valuable insights on the issue related to MPA management, and on the perception of stakeholders on the manner in which MPAs in Semporna should be managed. The findings are of benefit to Sabah Parks in understanding the underlying conflicts that exist in the current management practice, and the expectations of stakeholders, especially the local community. Moreover, the findings provide better insights on core issues of responsible MPA management in a general sense, which focus on the human factor, rather than purely on ecological factors. This would enable policy makers and institutions that manage MPAs to evaluate current practices of MPA management, and consider including social factors in their decision-making processes.